Practices of nurses towards people experiencing psychic crisis resulting from drug abuse - Deivson Wendell da Costa Lima; Mirya Karol Brasil Serafim; Francisco Rafael Ribeiro Soares; Antônia Líria Feitosa Nogueira Alvino; Alcivan Nunes Vieira; Magda Fabiana do Amaral Pereira (Universidade Federal de Santa Maria, 2018)
Aim: to understand the practices of nurses in urgent and emergency service for people experiencing psychic crisis resulting from drug abuse. Method: this is a descriptive research, with a qualitative approach, performed with 19 nurses who work in the emergency room of a general hospital in the countryside of Rio Grande do Norte. Data were collected through semi-structured interviews, and then submitted to content analysis. Results: nurses highlight that they focus on the signs and symptoms of the psychic crisis or use listening as an instrument of practice, and they also reported that the difficulties faced by them are the the prejudice against the drug user, the lack of training in the field of mental health and the inappropriate physical structure of the hospital. Conclusion: there is a need for nurses' qualification so that they can care for people who abuse drugs and for a greater engagement of the services that comprise the Psychosocial Care Network.